2011
DOI: 10.1007/s11676-011-0154-z
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation of microelement contents in leaves of Cyclocarea paliurus among the provenances

Abstract: Cyclocarya paliurus as a multiple function plant can accumulate biologically important microelement elements. To reveal the variation of selected microelement concentrations in leaves of C. paliurus provenances during the growing season, 12 C. paliurus provenances in the field trial were sampled five times at approximately 1-month intervals. The method of inductively coupled plasma optical emission spectrometer (ICP-OES) was employed to determinate average concentrations of Fe, Mn, Zn, Cu and Se in leaves of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The highest content was determined in XJP with 4.13 ± 0.04%, while the lowest was observed in SDP with 1.07 ± 0.07%. Many researchers have found that the content of bioactive compounds from plants varied significantly in different production areas (Fang, Chu, et al, ; Fang, Yang, et al, ). The essential oils of Pinus halepensis varied significantly in 10 production areas (Djerrad, Kadik, & Djouahri, ).…”
Section: Resultsmentioning
confidence: 99%
“…The highest content was determined in XJP with 4.13 ± 0.04%, while the lowest was observed in SDP with 1.07 ± 0.07%. Many researchers have found that the content of bioactive compounds from plants varied significantly in different production areas (Fang, Chu, et al, ; Fang, Yang, et al, ). The essential oils of Pinus halepensis varied significantly in 10 production areas (Djerrad, Kadik, & Djouahri, ).…”
Section: Resultsmentioning
confidence: 99%
“…Seven marker compounds in C. paliurus were positively identified by comparing the retention time, UV spectra and MS fragmentation with the corresponding data obtained from the analysis of reference compounds (Figure 3 (b)). In the previous studies, only isoquercitrin, kaempferol and quercetin have been used as marker compounds of C. paliurus (Fang et al, 2011;Yang et al, 2009;Xie et al, 2003). Although kaempferol-3-O-α-L-rhamnopyranoside , kaempferol-3-O-β-glucuronide (Zhang et al, 2005), arjunolic acid , cyclocaric acid B (Zhang et al, 2005) and pterocaryoside B (Cui and Li, 2012) have been identified as some compounds in C. paliurus, there are no reports on these compounds as markers in this plant.…”
Section: Analysis and Evaluation Of C Paliurus Samplesmentioning
confidence: 99%
“…To ensure the efficacy and safety of TCMs, qualitative and quantitative analysis of more major bioactive components is very important (Peng et al, 2013). The previous studies of C. paliurus have focused only on the quantification of total flavonoids (Mi et al, 2009;Chen et al, 2009;Jin et al, 2007) or a few selected flavonoids (kaempferol, quercetin and isoquercitrin) (Fang et al, 2011;Yang et al,2009;Xie et al, 2003) because many marker compounds are not commercially available, especially some characteristic compounds. The purposes of this study were to develop an effective method to extract the overall compounds and develop a simple HPLC analytical method to quantify seven major bioactive components (isoquercitrin, kaempferol-3-O-α-L-rhamnopyranoside, kaempferol-3-O-β-glucuronide, arjunolic acid, cyclocaric acid B, pterocaryoside B and pterocaryoside A) simultaneously.…”
Section: Introductionmentioning
confidence: 99%